2010
DOI: 10.2106/jbjs.i.00737
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Volar Plate Fixation of Articular Fractures of the Distal Part of the Radius

Abstract: The results of the present single-center study show that, following distal radial fracture fixation, wrist arthritis may affect the patient's subjective well-being, as documented with the Short Form-36, without influencing the functional outcome. Well-designed longitudinal clinical trials are needed to confirm the findings of the present investigation in terms of quality of life after surgical treatment of intra-articular distal radial fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 24 publications
5
45
1
1
Order By: Relevance
“…The majority of the studies have used subjective tools for measuring quality of life, such as the Gartland and Werley calculation and the DASH calculation while others have given greater emphasis to the radiographic parameters obtained after surgical reduction of fractures of the distal extremity of the radius. [7][8][9][10] In present study patients evaluated functionally by Mayo score and radiologically by Lidstrom classification. The average age of the patients in our study was 42.8 years.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of the studies have used subjective tools for measuring quality of life, such as the Gartland and Werley calculation and the DASH calculation while others have given greater emphasis to the radiographic parameters obtained after surgical reduction of fractures of the distal extremity of the radius. [7][8][9][10] In present study patients evaluated functionally by Mayo score and radiologically by Lidstrom classification. The average age of the patients in our study was 42.8 years.…”
Section: Discussionmentioning
confidence: 93%
“…The SF-36 has been translated into German and validated in Austria [28,29]. The instrument is comprised of 36 questions in eight different domains.…”
Section: Scalesmentioning
confidence: 99%
“…Grip strength was 78% of contralateral side and DASH score was 8.5. The report of 54 patients with intraarticular DRF and a mean age of 63 years by Gruber et al (2010) demonstrated 58 degrees of flexion, 57 degrees of extension, 83 degrees of pronation, 68 degrees of supination, grasping power was 71% of contralateral side at 6 years after surgery. DASH score was 5 points at 2 years follow up.…”
Section: Discussionmentioning
confidence: 95%